Association of Glycative Stress With Motor and Muscle Function - Egawa, Tatsuro; Hayashi, Tatsuya (Frontiers in Physiology, 2022)
Glycative stress is a type of biological stress caused by nonenzymatic glycation reactions, which include advanced glycation end product (AGE) formation, AGE accumulation, glycation-driven dysfunction of proteins and cellular signaling, inflammation, oxidation, and tissue damage. Increased glycative stress derived from hyperglycemia and lifestyle disorders is a risk factor in metabolic and age-related diseases, such as type 2 diabetes, cardiovascular disease, cancer, Alzheimer’s disease, osteoporosis, and dementia. Studies have shown that AGE accumulation is correlated with the age-related loss of muscle mass and power output, also called sarcopenia. Mechanistically, dysfunctions of contractile proteins, myogenic capacity, and protein turnover can cause glycative stress-induced skeletal muscle dysfunction. Because the skeletal muscle is the largest metabolic organ in the body, maintaining skeletal muscle health is essential for whole-body health. Increasing awareness and understanding of glycative stress in the skeletal muscle in this review will contribute to the maintenance of better skeletal muscle function.